Mitigation of water scarcity with sustained growth of Rice by plant growth promoting bacteria - Mahreen, Naima; Yasmin, Sumera; Asif, Muhammad; Yahya, Mahreen; Ejaz, Khansa; Mehboob-ur-Rahman,; Yousaf, Sumaira; Amin, Imran; Zulfiqar, Sana; Imran, Asma; Khaliq, Shazia; Arif, Muhammad (Frontiers in Plant Science, 2023)
Climate change augments the risk of food security by inducing drought stress and drastic decline in global rice production. Plant growth promoting bacteria (PGPB) have been known to improve plant growth under drought stress. Here in the present study, we isolated, identified and well characterized eight drought tolerant bacteria from rice rhizosphere that are tolerant to 20% PEG-8000. These strains exhibited multiple plant growth promoting traits i.e., 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity, exopolysaccharide production, phosphate (P) solubilizing activity (51-356 µg mL-1), IAA production (14.3-46.2 µg mL-1), and production of organic acids (72-178 µg mL-1). Inoculation of bacterial consortium (Bacillus subtilis NM-2, Brucella haematophilum NM-4 and Bacillus cereus NM-6) significantly improved seedling growth and vigor index (1009.2-1100) as compared to non-inoculated stressed plants (957-1046.7). Through rhizoscanning, efficiency of consortium was validated by improved root parameters such as root length (17%), diameter and surface area (18%) of all tested genotypes as compared to respective non-inoculated stressed treatments. Furthermore, response of consortium inoculation on three rice genotypes was positively correlated with improved plant growth and drought stress ameliorating traits by the accumulation of osmo-protectant i.e., proline (85.8-122%), relative-water-content (51%), membrane stability-index (64%) and production of antioxidant enzymes to reduce oxidative damage by reactive oxygen species. Decrease in temperature and improved chlorophyll content of inoculated plants were found using infrared thermal imaging and soil plant analyzer development (SPAD), respectively. The key supporting role of inoculation towards stress responses was validated using robust techniques like Infrared thermal imaging and Infrared gas analyzer. Furthermore, Principal Component Analysis depicts the contribution of inoculation on stress responses and yield of tested rice genotypes under water stress. The integration of drought tolerant rice genotype (NIBGE-DT02) and potential bacterial strains i.e., NM-2, NM-4 and NM-6 can serve as an effective bioinoculant to cope with water scarcity under current alarming issues related to food security in fluctuating climate.